Stad(t)t-Art : Kunst in 56 homöopathischen Dosen. - Avramidis, Joannis; Bandau, Joachim; Bergmann, Barbara; Bock, Ulrich; Brauhauser, William; Brunsiek, Sigrun; Brus, Johannes; Brusis, Ilse; Caspary, Gundula; Danne, Rainer; Dillenkofer, Sinje; Dose, Hanna; et al. (Bielefeld : Kerber Verlag Bielefeld, 1997)
Akiyama, Hiromi ; Avramidis, Joannis ; Bandau, Joachim ; Bert, Lore ; Bosslet, Eberhard ; Brauhauser, William ; Brus, Johannes ; Buchwald, Kurt ; Dillenkofer, Sinje ; El Loko ; Fischer, Lili ; Frisch, Mechtild ; Gerdes, Ludger ; Gräsel, Friedrich ; Gutbub, Edgar ; Hagebölling, Wilfried ; Isenrath, Hans-Paul ; Katase, Kazuo ; Kessl, Ulrike ; Kirschner, Wulf ; Klegin, Thomas ; Kowanz, Brigitte ; Laganovskis, Leonard ; Lasareishvili, Luka ; Maier, Nataly ; Mayer, Katharina ; Möckel, Ulrich ; van Munster, Jan ; Neugebauer, Ursula ; Neumann, Ekkehard ; Nierhoff, Ansgar ; Nishikawa, Katsuhiro ; Paik, Nam June ; Plessi, Fabrizio ; Pokorny, Werner ; Prager, Heinz-Günter ; Rabinowitch, David ; Rantzer, Philip ; Ratering, Werner ; Rheinsberg, Raffael ; Robbe, Wolfgang ; Roosen, Maria ; Schlichting, Dick ; Scott, Tim ; Simon, Klaus ; Steinbrenner, Hans ; Stolte, Mark ; Telljohann, Peter ; Tevet, Nahum ; Tunn, Susanne ; Uecker, Günther ; Ullman, Micha ; Ulrichs, Timm ; Visch, Henk ; Weiner, Willi ; Zhou Brothers
boek
Keywords: Duitsland